A COMPARATIVE STUDY of REQUEST STRATEGIES in BRITISH ENGLISH and UZBEK (Ustozlar uchun, 2026)
This comparative study investigates the request strategies employed by speakers of British English and Uzbek. It analyzes how cultural norms, social distance, and power dynamics influence the choice and formulation of requests in both linguistic contexts. Drawing on a corpus of naturally occurring conversations and discourse completion tasks, the research identifies similarities and significant divergences in directness, politeness markers, and mitigating devices. The findings offer insights into cross-cultural pragmatics and provide valuable implications for intercultural communication and language pedagogy.